The Influence of Brand Awareness on Purchase Decision With Social Media as an Intervening Variable: Penelitian - Zidny Ilma Hasan; Efti Novita Sari; Meli Siagawati; Muhammad Robby Reynaldy AlFaridzie; Sari Utami (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The evolution of digital technology has transformed how consumers interact with brands and make purchasing decisions. This study aims to analyze the impact of brand awareness on purchase decisions, with social media serving as an intervening (mediating) variable. A quantitative approach was employed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. Data were collected via an online survey targeting respondents who are active social media users and have previously purchased products online. The analysis is expected to demonstrate that brand awareness has a positive and significant effect on purchase decisions, both directly and indirectly through social media engagement. The role of social media as an intervening variable strengthens the relationship between brand awareness and the consumer's final purchasing decision. The practical implications of this study offer strategic guidance for marketers on optimizing social media content to bridge the gap between brand awareness and actual purchasing behavior.